Analisis Strategi Mitigasi Bencana Wilayah Pesisir Pantai Kuta dalam Menghadapi Ancaman Gelombang Tinggi dan Abrasi - Septia Arfina; Christina Renita Tampubolon; Evelyn Priscillia Br Sianipar; Anggie Vebry Purba; Gede Langgeng Adnyana; Friska Angelina Debataraja; I Made Dwi Guna Wijaya; Ni Kadek Mulan Anindita Prameswari; Iwan Deyal; Juene Merquis Wibowo; Suprabadevi Ayumayasari Saraswati (Program Studi Ilmu Kelautan, FIPAK, Universitas OSO, 2026)
Kuta Beach is a primary tourism icon in Bali currently facing serious environmental challenges in the form of high waves and progressive coastal abrasion. This study aims to analyze the current state of disaster risk in the Kuta Beach coastal area and evaluate the mitigation strategies implemented. Through field observations and interviews, it was found that abrasion has eroded the coastline by up to 20 meters, while high waves reach 2 to 4 meters, particularly during the June-August period. The impacts of these disasters include damage to pedestrian infrastructure and a decline in the economic productivity of local tourism actors. The study results indicate a gap between the community's emergency self-mitigation efforts and government policies, which are considered suboptimal. Integrated structural and non-structural mitigation measures are required to ensure the sustainability of the Kuta area.